pH-controlled protein orthogonal ligation using asparaginyl peptide ligases - Zhang, Dingpeng (2022)
Peptide asparaginyl ligases (PALs) catalyze transpeptidation at the Asn residue of a short Asn-Xaa1-Xaa2 tripeptide motif. Due to their high catalytic activity toward the P1-Asn substrates at around neutral pH, PALs have been used extensively for peptide ligation at asparaginyl junctions. PALs also bind to aspartyl substrates, but only when the γCOOH of P1-Asp remains in its neutral, protonated form, which usually requires an acidic pH. However, this limits the availability of the amine nucleophile and, consequently, the ligation efficiency at aspartyl junctions. Because of this perceived inefficiency, the use of PALs for Asp-specific ligation remains largely unexplored. We found that PAL enzymes, such as VyPAL2, display appreciable catalytic activities toward P1-Asp substrates at pH 4-5, which are at least 2 orders of magnitude higher than that of sortase A, making them practically useful for both intra- and intermolecular ligations. This also allows sequential ligations, first at Asp and then at Asn junctions, because the newly formed aspartyl peptide bond is resistant to the ligase at the pH used for asparaginyl ligation in the second step. Using this pH-controlled orthogonal ligation method, we dually labeled truncated sfGFP with a cancer-targeting peptide and a doxorubicin derivative at the respective N- and C-terminal ends in the N-to-C direction. In addition, a fluorescein tag and doxorubicin derivative were tagged to an EGFR-targeting affibody in the C-to-N direction. This study shows that the pH-dependent catalytic activity of PAL enzymes can be exploited to prepare multifunction protein biologics for pharmacological applications.